2018
DOI: 10.1016/j.jhep.2017.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Model projections on the impact of HCV treatment in the prevention of HCV transmission among people who inject drugs in Europe

Abstract: Measuring the amount of HCV in the population of PWID is uncertain. To reduce HCV infection to minimal levels in Europe will require scale-up of both HCV treatment and other interventions that reduce injecting risk (especially OST and provision of sterile injecting equipment).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
86
2
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 113 publications
(97 citation statements)
references
References 41 publications
4
86
2
4
Order By: Relevance
“…In Scotland, over 90% of new HCV infections occur among people who inject drugs (PWID) . HCV antibody prevalence among PWID is 58%, similar to other European countries …”
Section: Introductionsupporting
confidence: 70%
“…In Scotland, over 90% of new HCV infections occur among people who inject drugs (PWID) . HCV antibody prevalence among PWID is 58%, similar to other European countries …”
Section: Introductionsupporting
confidence: 70%
“…This mortality risk increases by another 1% annually in persons who continue to use intravenous drugs . Despite these data, modelling has suggested that treatment of HCV can reduce the prevalence of HCV in the reservoir of PWID and reduce the risk that a person new to or returning to injecting drugs after achieving SVR will come in contact with HCV and become infected or reinfected . A prospective study which demonstrates that such modelling is actually correct would be extremely useful for our elected officials who must provide funding to support these types of programmes.…”
Section: Treatment Of Hcv In Patients Who Inject Drugsmentioning
confidence: 99%
“…In western Europe, there are an estimated 1 009 500 (0.34% of the total population) PWID between 15 and 64 years of age . Treatment scale‐up has been identified as a requirement in order to achieve a reduction, or even the elimination, in HCV prevalence in most European countries …”
Section: Introductionmentioning
confidence: 99%